2018
DOI: 10.1111/jpn.13024
|View full text |Cite
|
Sign up to set email alerts
|

Total nutrient digestibility and small intestine starch digestion in Nellore and Angus young bulls fed a whole shelled corn diet

Abstract: Eighteen Nellore and 18 Angus young bulls with BW of 381 ± 12 kg were randomly assigned into two feeding groups (whole shelled corn [WSC] or ground corn with silage [GC]) to evaluate the interaction of breed and diet on total nutrient digestibility, pancreatic α‐amylase, and maltase activity and SLC5A1expression in the small intestine. Experimental diets (DM basis) included (a) a diet containing 30% corn silage and 70% GC and soya bean meal‐based concentrate and (b) a diet containing 85% WSC and 15% of a soya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Moreover, Angus bulls had greater G:F than Nellore bulls (P < 0.01). These results may be explained by the better use of starch in the gastrointestinal tract of Angus bulls compared with Nellore bulls (Carvalho, 2015).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, Angus bulls had greater G:F than Nellore bulls (P < 0.01). These results may be explained by the better use of starch in the gastrointestinal tract of Angus bulls compared with Nellore bulls (Carvalho, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…Chemical analyses of the diets were performed according to the Association of Official Analytical Chemists (1990) for CP (method 920.87), Sniffen et al (1992). 5 ME = TDN (g/kg DM) × 4.4 × 0.82 (Carvalho, 2015).…”
Section: Performance and Behavior Studymentioning
confidence: 99%
“…In this study, the NDF content was not affected by an increase in alfalfa input level (571, 558 and 562 g/kg for AH0, AH15 and AH30, respectively, p > .1), which might be the main reason for the similar DM intake between the benchmark and alfalfa diets. Meanwhile, compared with concentrate, the longer particles of alfalfa increased the rumination and salivation of animals, which also contributed to similar DM intake (Carvalho et al, 2019). Note: a, b and c: means within the same row and with the same letters are not significantly different (p > .05).…”
Section: Intake and Tract Apparent Digestibilitymentioning
confidence: 93%
“…Studies have shown that the problem of low microbial protein yield with poor-quality roughage-based diets cannot be simply solved or completely compensated by supplementation with high amounts of concentrates (Pathak, 2008), and high concentrate input also increases the risk of metabolic disorders (Tayyab, Wilkinson, Charlton, Reynolds, & Sinclair, 2019). Meanwhile, steadily increasing the demand for milk and meat much coming from ruminants would increase the proportion of food used as feed against the background of limited available arable land and further exacerbation of global climate change, with more than 13.3% of the world's cereal grains being offered to ruminants (Eisler et al, 2014) and with this proportion increasing in areas such as Brazil (Carvalho et al, 2019) and China. Meanwhile, steadily increasing the demand for milk and meat much coming from ruminants would increase the proportion of food used as feed against the background of limited available arable land and further exacerbation of global climate change, with more than 13.3% of the world's cereal grains being offered to ruminants (Eisler et al, 2014) and with this proportion increasing in areas such as Brazil (Carvalho et al, 2019) and China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation